2000
DOI: 10.1038/35044100
|View full text |Cite
|
Sign up to set email alerts
|

Binding of disease-associated prion protein to plasminogen

Abstract: Transmissible spongiform encephalopathies are associated with accumulation of PrP(Sc), a conformer of a cellular protein called PrP(C). PrP(Sc) is thought to replicate by imparting its conformation onto PrP(C) (ref. 1), yet conformational discrimination between PrP(C) and PrP(Sc) has remained elusive. Because deposition of PrP(Sc) alone is not enough to cause neuropathology, PrP(Sc) probably damages the brain by interacting with other cellular constituents. Here we find activities in human and mouse blood whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 203 publications
(139 citation statements)
references
References 19 publications
6
131
1
1
Order By: Relevance
“…supported by experiments showing that FabЈ fragments of some of these antibodies failed to immunoprecipitate PrPsc. This is not surprising taking into account that several proteins and polymers have already been shown to bind SAFs, including serum proteins (12), heparan sulfates (13,14), and nucleic acids (4,15). In addition, we show that a significant PrPsc immunoprecipitation can be obtained even with BSA-coated beads in appropriate conditions.…”
Section: Discussionsupporting
confidence: 71%
“…supported by experiments showing that FabЈ fragments of some of these antibodies failed to immunoprecipitate PrPsc. This is not surprising taking into account that several proteins and polymers have already been shown to bind SAFs, including serum proteins (12), heparan sulfates (13,14), and nucleic acids (4,15). In addition, we show that a significant PrPsc immunoprecipitation can be obtained even with BSA-coated beads in appropriate conditions.…”
Section: Discussionsupporting
confidence: 71%
“…Improved diagnostic tests could now be developed using a new cyclic amplification procedure, which is capable of efficiently amplifying minute amounts of PrP Sc in brain tissue (37). Coupled with a reagent that specifically binds to PrP Sc , such as the recently identified plasminogen (38), this might reveal the levels of prion infectivity looming in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators reported mouse Rocky Mountain Laboratory (RML) prions bind to plasminogen (38), but subsequent studies by others demonstrated that the affinity of PrP for plasminogen is low (M. Vey, personal communication; see ref. 39).…”
Section: Prions In Bloodmentioning
confidence: 99%